IMPLEMENTASI GOOD LOCAL GOVERNANCE DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH MELALUI PENERAPAN SISTEM AKUNTABLITAS KINERJA PEMERINTAH - to, Suryan (Jurnal Borneo Administrator, 2007)
One of the public demands toward all governance organizer in the region is their ability to deliver the responsibility (accountability) for the entire mandate which have been entrusted on them. Responding this demand, the government have issued Inpres No. 7 Year 1999 on AKIP and followed up by the decree of LAN’s Head No.239/IX/6/8/2003 about Improving the guidance of AKIP Report. The problem is whether the subject of LAKIP arrangement is in harmony with other regulation like Law No. 25 Year 2004 about SPPN and Law No. 32 Year 2004 about Local Governance? This brief article aims to insist various party to immediately publish the result of Inpres No. 7 Year 1999 revision, and it is, at once, a hope that public accountability can be realized to reach good local governance.  Keywords: accountability system, LAKIP, good governance.